Breaking Bad: How Viruses Subvert the Cell Cycle - Fan, Ying; Sanyal, Sumana; Bruzzone, Roberto (Frontiers in Cellular and Infection Microbiology, 2018)
Interactions between the host and viruses during the course of their co-evolution have not only shaped cellular function and the immune system, but also the counter measures employed by viruses. Relatively small genomes and high replication rates allow viruses to accumulate mutations and continuously present the host with new challenges. It is therefore, no surprise that they either escape detection or modulate host physiology, often by redirecting normal cellular pathways to their own advantage. A diverse array of strategies and molecular targets are used by viruses to subvert host cellular processes, while evading detection. These include cell-cycle regulation, major histocompatibility complex-restricted antigen presentation, intracellular protein transport, apoptosis, cytokine-mediated signaling, and humoral immune responses. Among others, manipulation of the host cell cycle is routinely employed by viruses to create a favorable environment for replication, largely by deregulating cell cycle checkpoints. This review is centered on our current understanding of the molecular aspects of cell cycle regulation that are often targeted by viruses. Further study of their interactions should provide fundamental insights into cell cycle regulation and improve our ability to exploit these viruses.